Effective leadership behaviors in the sales functions of consumer driven business in South Africa - Hughes, Steven (My University, 2013)
Leadership as a topic provides an extensive challenge in that its scope is significant and no ‘one size fits all’ approach exists. Within leadership, there are various theories and styles. Potential leaders all have a natural style of leadership that they gravitate towards; nevertheless, it does not mean that leaders cannot grow. They have the ability to learn to lead more effectively by practising, observing and adjusting their behaviour where necessary. This research report aims to identify business leaders’ perceptions of the key behaviours that determine effective leadership within sales functions of consumer driven businesses in South Africa by using Nicholls’ (1994) Head, Heart and Hands framework, which allows for differentiation between various types of behaviour. A themed content analysis was conducted on the responses and information (interview transcripts) gathered from 16 critical incident interviews involving 16 respondents with current or recent sales director experience, thus meeting the research criteria. The common factors identified across all respondents led to a deeper understanding of the issues, resulting in a list of themes, categories within those themes and key behaviours of effective leaders relative to behaviours of effective leaders within sales functions of consumer driven businesses. The most significant feature of the research was that provided a leader leads by example and treats people in the manner in which they would wish to be treated, it would be difficult to make fundamental leadership mistakes. By being authentic in their leadership style, and being themselves they will ‘always’ do the right thing and make the right decisions. Therefore, sales directors and aspiring leaders within the sales function of consumer driven industries can learn and apply the key behaviours of a leader, which is significantly easier to change and adapt than characteristics of a leader. Furthermore, the literature review revealed that leadership behaviour plays an extensive role in the performance and general productivity of the work force. The results of the research study have identified key behaviours of effective leaders within the sales functions of consumer driven businesses in South Africa.
MBA thesis
Keywords: Leadership; Sales and selling; Authentic leadership